143k views
0 votes
Solve by your method of choice.

Solve by your method of choice.-example-1
User Pumbo
by
4.7k points

1 Answer

4 votes

Answer:

B

Explanation:

Given the 2 equations

x³ + y = 0 → (1)

11x² - y = 0 → (2)

Add (1) and (2) term by term to eliminate the term in y

x³ + 11x² = 0 ← factor out x² from each term

x²(x + 11) = 0

Equate each factor to zero and solve for x

x² = 0 ⇒ x = 0

x + 11 = 0 ⇒ x = - 11

Substitute these values into (1) for corresponding values of y

(1) y = - x³

x = 0 ⇒ y = 0 ⇒ (0, 0) is a solution

x = - 11 ⇒ y = - (- 11)³ = 1331 ⇒ (- 11, 1331) is a solution

User Jude Allred
by
4.7k points